luxRI homologs are universally present in the genus Aeromonas - Patole Milind S; Kong Richard; Jangid Kamlesh; Shouche Yogesh S (BMC Microbiology, 2007)
Abstract Background Aeromonas spp. have been regarded as "emerging pathogens". Aeromonads possess multifactorial virulence and the production of many of these virulence determinants is associated with high cell density, a phenomenon that might be regulated by quorum sensing. However, only two species of the genus are reported to possess the luxRI quorum sensing gene homologs. The purpose of this study was to investigate if the luxRI homologs are universally present in the Aeromonas strains collected from various culture collections, clinical laboratories and field studies. Results Of all the 73 Aeromonas strains used in the study, seventy-one strains elicited acyl-homoserine lactone-mediated response in multiple biosensor strains. However, dot blot hybridization revealed that the luxRI homologs are present in all the strains. PCR amplification and sequencing revealed that the luxRI homologs shared a very high percentage sequence similarity. No evidence for lateral gene transfer of the luxRI homologs between aeromonads and other genera was noted. Conclusion We propose that the luxRI quorum sensing gene homologs are universally present in the genus Aeromonas independently from their origin. This study is the first genus-wide report of the taxonomic distribution of the luxRI homologs.